Surgeon’s imposter syndrome: a systematic review - El Boghdady Michael; Ewalds-Kvist Béatrice (Springer Science and Business Media LLC, 2025)
INTRODUCTION
Imposter syndrome (IS) refers to the psychological experience of imagining that one's achievements do not originate from one's own authentic competence. Surgeons are constantly faced with life-threatening decisions and can easily feel inadequate or insecure despite their years of training and experience. Imposter syndrome can distress surgeons at all career stages and has profound psychological and professional consequences. We aimed to review imposter syndrome in surgeons.
METHODS
A systematic search was performed in compliance with The PRISMA checklist. Search was performed in the PubMed and ScienceDirect databases. We included articles about IS in surgeons. We excluded narrative articles, commentaries and studies involving medical students or other specialties. Citations were quality assessed by MERSQI and evidence graded (GRADE). Risk of bias was assessed among the included citations.
RESULTS
The search revealed 695 citations, from which a final list of 12 was compiled after applying the inclusion and exclusion criteria. Participants included trainees and consultant surgeons across various surgical specialties. The following research questions were answered: Are surgeons with IS predisposed to mental or physical challenges? Do surgeons experience gender differences in IS? Can the feeling of IS be reduced?
CONCLUSION
There is a high prevalence of imposter syndrome among surgeons. Surgeons with IS are predisposed to experience mental or physical challenges. Female surgeons experience IS more frequently than their male counterparts. Feelings of IS can decline with increasing age but also with other included methods. Risks and multiple preventative measures were explored. The key to reducing IS is to train oneself to discern fact from fiction, thereby undermining distorted thoughts that perpetuate feelings of being an imposter.